PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PEMBALUT MEREK KOTEX DI KOTA BATAM - Syarifah Aini Ma'ruf; Tiurniari Purba (SCIENTIA JOURNAL, 2026)
This study aims to analyze the influence of product quality and brand image on purchasing decisions for Kotex brand sanitary napkins. This study used a quantitative approach with a survey method of 100 respondents who used Kotex sanitary napkins. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis with t-tests and F-tests. The results showed that partially, product quality had no significant effect on purchasing decisions, while brand image had a significant effect on purchasing decisions for Kotex brand sanitary napkins. Simultaneously, product quality and brand image had a significant effect on purchasing decisions. This finding indicates that brand image plays a more dominant role than product quality in driving consumer purchasing decisions.